Green Halal Fashion: Integrasi Prinsip Keberlanjutan dan Syariat Islam dalam Industri Fashion Muslim Indonesia - Nurul Jannah (Universitas Islam Raden Rahmat, 2026)
This study examines the influence of perceived green value, Islamic environmental ethics, halal brand trust, and modest fashion consciousness on the purchase intention of green halal fashion products among Indonesian millennial Muslim consumers. Using a quantitative approach with a cross-sectional survey design, data were collected via a structured questionnaire from 385 millennial Muslim fashion consumers (aged 18–38 years) in six major cities in Indonesia. Sampling was conducted using purposive sampling, and the data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4.0 software. The results indicate that green perceived value, Islamic environmental ethics, halal brand trust, and modest fashion consciousness have a significant positive effect on purchase intention. The model as a whole explains 61.4% of the variance in green halal purchase intention (R² = 0.614). A mediation test revealed that Islamic environmental ethics partially mediates the relationship between halal brand trust and green perceived value. This study concludes that green perceived value and Islamic environmental ethics are the most influential determinants of purchase intention for green halal fashion products, and formulates the Green-Halal Fashion Triangle model as an integrative conceptual framework.